Preliminary Study on Wireless Home Automation Systems with Both Cloud-Based Mode and Stand-Alone Mode - Zhibo Pang; Yuxin Cheng; Johansson, Morgan E.; Bag, Gargi (2014 IEEE 17th International Conference on Computational Science and Engineering, 2014)
As the Smart Home segment is an intersection of numerous industries including consumer electronics, telecom, internet, and building automation, a Home Automation (HA) system requires flexible wireless communication architecture to not only take the advantages of wireless technologies such as reduced cost of installation and maintenance and improved user experiences but also fulfill the concerns of various industrial stakeholders. From this point-of-view, neither the pure Cloud-Based nor the Stand-Alone architecture is sufficient. In this paper, an IP-based hybrid architecture is presented which can support flexible combination of Could-Based Mode and Stand-Alone Mode. Preliminary prototyping based on the 6LoWPAN and experimental evaluation of performances have indicated the technical feasibility as well as future directions of improvement.